Modified body mass index and time interval between diagnosis and operation affect survival after liver transplantation for hereditary amyloidosis: a single-center analysis - Franz, Clemens; Hoffmann, Katrin; Hinz, Ulf; Singer, Reinhard; Hund, Ernst; Gotthardt, Daniel; Ganten, Tom M.; Kristen, Arnt; Hegenbart, Ute; Schönland, Stefan; Hinderhofer, Katrin; Büchler, Markus W.; et al. (Clinical transplantation, 2013)
Introduction Familial amyloid polyneuropathy (FAP) is the most common subtype of hereditary amyloidosis. The amyloid protein transthyretin deposits as rigid amyloid fibers in the extracellular matrix of various tissues including peripheral nerves, heart, and gastrointestinal tract. As the mutated amyloid protein is mainly produced in the liver, one form of treatment to halt the progression of disease is liver transplantation (LT). This study was performed to identify risk factors for decreased overall survival. Methods Clinical data of 21 transplant patients who underwent LT for FAP between 1996 and 2011 were analyzed retrospectively. Results The majority of patients had cardiac symptoms (76%), gastrointestinal symptoms (71%), or peripheral polyneuropathy (71%). A conventional operating technique was performed on 11 patients using end-to-end caval anastomoses, while the modified piggyback technique by Belghiti was performed on 10 patients. Overall survival analysis revealed a one-yr survival rate of 74.3% and three- and five-yr survival rates of 60.0% and 52.5%, respectively. Pre-operative modified body mass index (mBMI) <700 kg g/L m² and time interval between diagnosis and operation before LT resulted in significantly lower overall survival (p = 0.0137; p = 0.033). Conclusion The pre-operative nutritional status and time interval between diagnosis and operation before LT influence overall survival after LT for hereditary amyloidosis.
Gesehen am 30.04.2021